First report of the root-knot nematode Meloidogyne incognita on Salvia miltiorrhiza Bunge in Henan Province, China - Wen, Yi (Plant disease, 2022)
Salvia miltiorrhiza Bunge is an important Chinese herbal medicine, mainly used to treat cardiovascular disease. At present, the planting area of S. miltiorrhiza is near 20,000 hectares in China, mainly in Shandong, Henan, Shanxi, Shaanxi and Sichuan provinces. Root-knot nematode (Meloidogyne spp.) is one of the most devastating pathogens on S. miltiorrhiza. In November 2020, we observed that some S. miltiorrhiza plants grew poorly with smaller, fewer and chlorotic leaves and even necrosis on some middle and lower ones in a Chinese herbal medicine planting base (34° 4' 11.52'' N; 113° 25' 51.40'' E) in Yuzhou City, Henan Province, China. Furthermore, the galls and egg masses were visible on the roots of S. miltiorrhiza, which were the typical symptoms caused by root-knot nematodes. Ten samples of galled roots and rhizosphere soils were collected, bagged and taken to the lab for tests. Females and J2s were extracted from these samples. White, pear-shaped females were observed in the roots, and the average number of second-stage juveniles (J2s) was 121.5 ± 10.8 per 100 ml of soil. The perineal patterns of females showed a high dorsal arch, which was either square or trapezoid with either smooth or wavy striae and without obvious lateral lines. The main morphometrics of females (n=20, mean ± SE; range) were as follows: body length (L)  = 609.0  ±  62.5 μm (492.4 to 716.4 μm); maximum body width (W) = 377.0  ±  28.6 μm (329.7 to 436.1 μm); stylet length  =  17.0  ±  1.8 μm (14.2 to 20.5 μm); and distance from dorsal esophageal gland orifice to stylet knobs (DGO) =  3.3  ±  0.3 μm (2.8 to 3.9 μm). The J2s were in vermiform, and stylet knobs were prominent and rounded. The tail of J2s possessed a transparent area with an obtuse tip. J2s (n  =  20) were measured (mean ± SD; range) as follows: L  =  401.2  ±  29.3 μm (358.2 to 456.1 μm); W = 14.1 ± 1.1 µm (12.5 to 16.0 µm); L/W  = 28.6  ±  1.0 (26.7 to 30.4); stylet length =  10.3  ±  0.6 μm (9.1 to 11.2 μm); DGO  =  2.4  ±  0.1 μm (2.1 to 2.6 μm); and tail length  =  49.3  ± 2.8 μm (45.2 to 54.7 μm). All the key morphometrics were similar to those of the M. incognita population described by Song et al. (2019). The PCR amplifications of rDNA-internal transcribed spacer (ITS) fragments generated an amplicon of 544 bp from a single female or/and J2s (n = 22) using the universal primers M18S (5'-AACCTGCTGCTGGATCATTAC-3') and M28S (5'-GTATGCTTAAGTTCAGCG-3') (Feng et al. 2010). The PCR amplifications were repeated five times for each sample, and the products were purified and sequenced. The obtained sequnce was deposited in GenBank with Acc. No. OM304617.1. The amplified ITS region sequence was identical to those of M. incognita from India (KT869139.1) and China (MT490926.1 and MT071559.1). For confirmation, the primers species-specific for M. incognita (Inc-K14-F, 5'- GGGATGTGTAAATGCTCCTG -3' and Inc-K14-R, 5'- CCCGCTACACCCTCAACTTC -3') were further used for amplification. Expected PCR amplicon of 399 bp was acquired, which was consistent with previous report for M. incognita (Randig et al. 2002). Pathogenicity and reproduction of this M. incognita population on S. miltiorrhiza was confirmed and examined. Seeds of S. miltiorrhiza were sown in the pots filled with 200 ml of autoclaved soil mixture (loamy soil/sand, 1:1). Two weeks later, a total of 12 plants were inoculated each with 400 J2s, which were hatched from a field-derived M. incognita population. Four plants without nematode inoculation were used as the control. The plants grew in a chamber at 25/30 °C under 12-h dark/12-h light conditions. The parasitic J2s, J3s, J4s and females in roots were observed under a stereomicroscope at 5, 15 and 30 days post inoculation (dpi). At 35 dpi, an average of 98.3 ± 15.7 galls and 23.8 ± 6.9 egg masses per S. miltiorrhiza plant were counted, and the root gall index reached 6 according to the 0-10 RKN rating scale (Poudyal et al. 2005). Nematodes were re-isolated from the roots and their morphological and molecular characteristics were identical to the nematodes obtained from the original samples. Furthermore, all the inoculated S. miltiorrhiza roots showed typical RKN galls with the same symptoms as those initially observed in the field. No symptoms were developed on the non-inoculated control plants, and from which no nematodes were isolated. The nematode on S. miltiorrhiza was therefore certified as M. incognita. Han et al. (2019) isolated and morphologically identified M. incognita from the roots of S. miltiorrhiza and Trichosanthes kirilowii Maximin in Changqing area of Shandong Province, China, but did not perform the Koch's Rule. To our knowledge, this is the first formal report of M. incognita infecting S. miltiorrhiza in Henan Province, China. With the increase of Chinese herbal medicine planting area, plant parasitic nematodes are becoming more and more serious and have become an limiting factor on medicinal plant production, and the yield losses can be as high as 70%. This finding provides important and solid information for growers of Chinese medicinal plants, based on which suitable management action should be taken